2009
DOI: 10.1364/josab.26.00b161
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterials: transforming theory into reality

Abstract: Metamaterials constitute a new area of science that is expanding our fundamental understanding of the behavior of the propagation of electromagnetic waves and their interactions, and providing new solutions for a wide range of applications from optical communications and defense to biological imaging. In this brief review, we focus on recent progress in theoretical, numerical, and experimental studies of linear and nonlinear optical properties of negative index materials and in the emerging field of transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 92 publications
(127 reference statements)
0
16
0
Order By: Relevance
“…MMs have an abundance of applications, fabrication schemes, and designs, all of which depend of the particular bandwidth of interest, and desired functionality. Optical MMs have been extensively studied, both theoretically and experimentally 2,3,4 . In the visible region of the E-M spectrum, metals such as gold and silver are most commonly used 3 .…”
Section: Introductionmentioning
confidence: 99%
“…MMs have an abundance of applications, fabrication schemes, and designs, all of which depend of the particular bandwidth of interest, and desired functionality. Optical MMs have been extensively studied, both theoretically and experimentally 2,3,4 . In the visible region of the E-M spectrum, metals such as gold and silver are most commonly used 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with recent advances in nanofabrication technologies, it is also possible to construct an electromagnetic resonator by taking a plasmonics oriented approach, i.e., using nanostructures made with metals and working in the optical regime [2]. Both the physical understanding and the technical implementation of these two different categories of electromagnetic resonators have been well developed; however, due to the emergence of the new concept of metamaterials in microwave engineering and optics [3][4][5][6][7][8], currently there still exist a significant amount of related research interests . A noticeable example that represents the progress of microwave engineering oriented electromagnetic resonators is given by Engheta [9], who theoretically showed that the size of a one-dimensional electromagnetic resonator can be reduced into the subwavelength regime by inserting a pair of righthanded and left-handed slabs into a space sandwiched between two perfectly conducting parallel planes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, plasmonic photonic crystals have a large refractive index contrast and can be classified as strongly modulated photonic crystals, which exhibit interesting refractive properties, such as negative refraction [41], as demonstrated for all-dielectric 2D [42][43][44] and 3D [45,46] photonic crystals. In metallodielectric crystals, however, negative refraction is usually attributed either to the simultaneous existence of an electric and a magnetic resonance or to the anisotropy of the crystal [47]. The former case can be realized, e.g., in assemblies of metalcoated spheres made of a polar material characterized by a resonant permittivity function [48][49][50].…”
Section: Introductionmentioning
confidence: 99%